2002
DOI: 10.1149/1.1516776
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Anodic Overvoltage Observed during Fluorine Evolution in KF-2HF

Abstract: International audienceThe kinetics of the fluorine evolution reaction was studied in molten KF-2HF with a horizontal disk electrode in a large potential window. A new model was proposed recently for representing the electrode/electrolyte interface; it includes the presence of a "fluidized" layer between the surface carbon-fluorine film (C-F) generated on the carbon anode during electrolysis and the fluorine gas film. This model was confirmed here to be consistent. The fluidized layer is composed of liquid KF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…This is not surprising when looking at Equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) since the four forces acting on bubble speed depend on the diameter in a non-linear way. Figure 6 shows the variation in current efficiency with the hydrogen bubble diameter for a cell current density Io.…”
Section: Variation In Current Efficiency With Bubble Diametermentioning
confidence: 94%
See 1 more Smart Citation
“…This is not surprising when looking at Equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) since the four forces acting on bubble speed depend on the diameter in a non-linear way. Figure 6 shows the variation in current efficiency with the hydrogen bubble diameter for a cell current density Io.…”
Section: Variation In Current Efficiency With Bubble Diametermentioning
confidence: 94%
“…Fluorine electrolysis [1][2][3] is particularly interesting because overpotentials are very large, thermal phenomena are significant [4,5], fluorine emission is not conventional and free convection makes the temperature uniform in the cell [1]. The characteristics of fluorine bubble release are not yet completely understood and a specific study is in progress.…”
Section: Introductionmentioning
confidence: 99%
“…characteristics of fluorine bubble release are not yet completely understood [1,4]. The two-phase free flow is mainly due to hydrogen bubbles evolving at the cathode, but large fluorine bubbles also take part in the two-phase movement, as seen in fig.…”
mentioning
confidence: 99%
“…H. Roustan [1] has shown that to some extent the large gliding fluorine bubbles drag the electrolyte up along the anode. A numerical model was gradually developed in France to account for all the strongly linked phenomena involved in fluorine electrolysis [2][3][4][5][6]. The final numerical model combined two commercial codes, Flux-Expert (FE) and Estet-Astrid (EA), both distributed by Astek [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation